Mirrored - Flinn, Alex (HarperTeen, an imprint of HarperCollinsPublishers, 2015)
A modern, multi-generational tale of Kendra, the witch from "Snow White," who trains Violet, an ugly, lonely, and heartbroken girl in the 1980s who transforms herself into "the fairest one of all" but still cannot win Greg's heart, and Celine, Greg's daughter with Violet's high school rival, Jennifer.